Nickel(II)- and Silver(I)-Catalyzed C–H Bond Halogenation of Anilides and Carbamates - Kianmehr, Ebrahim; Afaridoun, Hadi (Synthesis, 2020)
ortho-C–H bond halogenation of anilides and N-aryl carbamates using easily available N-halosuccinimides (NXS) as the active halogenation reagent in the presence of nickel or silver catalyst has been developed. This method provides a new approach to 2-haloanilides and carbamates, which may serve as starting materials for the synthesis of pharmaceutically and biologically active compounds.
Keywords: cross-coupling reactions; C–H activation; homogeneous catalysis; halogenation; nickel; silver